Прапорнича традиція Прилуцького полку другої половини XVIII ст. - Савчук, Ю. (Спеціальні історичні дисципліни: питання теорії та методики, 2019)
У 2002–2007 рр. у кількох числах «Спеціальних історичних дисциплін: питання теорії та методики» автором здійснено серію наукових публікацій щодо ґенези та реформування прапорничої традиції збройних сил Гетьманату у другій половині XVIIІ ст. У фокусі дослідницької уваги виявилися прапори Стародубського, Ніжинського, Чернігівського та Гадяцького полків. Окремо з’явилася праця на матеріалах Лубенського полку. Після тривалої перерви — у 2014–2015 рр. було опубліковано наукові розвідки щодо решти реєстрових полків Гетьманату — Київського, Переяславського, Полтавського та Миргородського. Дана стаття присвячена сотенним та полковим прапорам Прилуцького полку, який займає дещо осібне місце у цьому ряду. Джерельна база Прилуцького полку з досліджуваної тематики є відносно вужчою ніж в інших реєстрових полках (окрім Полтавського та Миргородського). Ротація сотенних та полкових прапорів тут відбулася у винятковий спосіб: одночасно та стовідсотково. Одноактна дія позбавила істориків можливості реконструкції багатьох важливих нюансів процесу прапоротворення. Разом з тим, виявлені джерела суттєво доповнюють загальну картину прапоротворення у збройних силах Гетьманату та є носіями вкрай цінної вексилологічної інформації. Представлена нижче стаття, як і попередні публікації, опирається на вже апробовані методологію, та схему викладу матеріалу. In 2002–2007 in several issues of "Special Historical Disciplines: Questions of Theory and Methodology" the author carried out a series of scientific publications on gender and reforming the flag traditions of Hetman's armed forces in the second half of the XVIII century. In the focus of research attention there were flags of Starodub, Nizhyn, Chernihiv and Hadyach Regiments. The work separately appeared on materials of the Lubny Regiment. After a long break — in 2014–2015 was posted scientific intelligence concerning the rest of the registry Regiments of Hetmanate — Kyiv, Pereyaslav, Poltava and Myrhorod. This article is devoted to sotnya and regiment banners of Pryluky Regiment, which occupies a somewhat settled place in this row. The source base of the Pryluky Regiment from the investigated subjects is relatively narrow than in other registry regiments (except Poltava and Myrhorod). The rotation of the sotnya and regiment banners here took place in an exceptional way: at the same time and for one hundred percent. One-act action was deprived of historians the possibility of reconstruction of many important nuances of the process of praporopoiesis. However, the found sources substantially complement the overall picture of the primordial formation in the armed forces of the Hetman and are carriers of highly valuable vexilology information. The article presented below, as well as previous publications, relies on already tested methodology, and the scheme of presentation material. The material is a new study. The findings are first published in the scientific community. Flags research continues. The findings will be verified and documented in the following publications. New materials are being processed.